Investigation on the effect of Bismuth concentration towards radiation shielding properties in Ag-embedded Borobismuthate mixed ionic electronic glass system / Nurul Atika Mohd Khalid ... [et al.] - Mohd Khalid, Atika; Mohd Rejab, Mazwani; Mansor, Muhammad Naaim; Hisam, Rosdiyana (Research Management Institute (RMI), 2023)
In this study, 20Li2O-xBi2O3-(79-x)B2O3-1Ag glasses for x=3,5,7,9, and 11 mol % glasses were prepared by using the melt quenching technique to investigate radiation shielding properties of the glasses using Phy-X/PSD simulation program at 15 keV to 15 MeV photon energy range. The radiation shielding parameters were carried out to determine the mass attenuation coefficient (MAC), linear attenuation coefficient (LAC), half value layer (HVL), mean free path (MFP) and effective atomic number (Zeff). The results showed that the Bi2O3 addition has improved overall radiation shielding properties. The MAC of the glass system was increased as Bi2O3 concentration increased. The HVL showed that present glass better than standard commercial concretes as lower HVL value indicates better shielding where 11 mol % required a much smaller thickness than 3 mol %. Therefore, sample with highest bismuth content has the most effective radiation protective property. Smaller MFP is most preferable as it suitable for protection materials; indicated the 11 mol % is best candidate for radiation shielding. Lastly, the higher value in Zeff was contributed by higher atomic number of Bi over B; thus, enhanced protection performance.